2020
DOI: 10.3390/ijerph17176133
|View full text |Cite
|
Sign up to set email alerts
|

Early Rehabilitation after Surgical Repair of Medial and Lateral Collateral Elbow Ligaments: A Report of Three Cases

Abstract: Elbow ligament injuries are commonly caused by overuse; degeneration; and trauma; such as from a fall or collision. The purpose of this study was to present the results of three cases involving patients undergoing early rehabilitation after surgical treatment for complex injury of the elbow medial collateral ligament (MCL) and lateral collateral ligament (LCL). Two patients were non-athlete middle-aged women and one was a recreational judo player. Surgery was performed through open incision or arthroscopically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 29 publications
(51 reference statements)
0
9
0
1
Order By: Relevance
“…Through the simple analysis of the motion waveforms of the two subjects, it is concluded that the motion completed by subject 1 during the knee health-monitoring period is better than that of subject 2. After the subject completes the test of the knee health monitoring system, the knee joint health monitoring results of some subjects are obtained, as shown in Table 2 [22][23][24].…”
Section: Experimental Results and Analysismentioning
confidence: 99%
“…Through the simple analysis of the motion waveforms of the two subjects, it is concluded that the motion completed by subject 1 during the knee health-monitoring period is better than that of subject 2. After the subject completes the test of the knee health monitoring system, the knee joint health monitoring results of some subjects are obtained, as shown in Table 2 [22][23][24].…”
Section: Experimental Results and Analysismentioning
confidence: 99%
“…This suggests that forearm length may impact the pain classification of EP patients, with a shorter forearm length being associated with lower levels of EP pain [48,49]. Therefore, based on the EP assessment scoring criteria, we recommend that EP patients with slight pain should undergo unloaded or lightly loaded upper limb strength training, such as isometric training, to improve arm muscle strength and endurance around the elbow joint, as an intervention method rather than relying solely on medication [50][51][52]. For EP patients with critical pain, they should exercise caution when selecting potential intervention methods.…”
Section: Discussionmentioning
confidence: 99%
“…We set up the rehabilitation program following the evidence on the elbow rehabilitation (Fusaro et al., 2014; Kim et al., 2020; Manocha et al., 2017; Pipicelli & King, 2020; Schubert et al., 2021; Szekeres & King, 2006; Wilk & Arrigo, 2020). The elbow tends to become stiff after surgery or trauma; therefore, rehabilitation should balance the need for an early mobilisation and healing of the injured or operated tissues (Fusaro et al., 2014; Kim et al., 2020; Manocha et al., 2017; Pipicelli & King, 2020; Wilk & Arrigo, 2020). Firstly, the goals were to reduce aedema and inflammation with early recovery of range of motion (Fusaro et al., 2014; Kim et al., 2020; Manocha et al., 2017; Pipicelli & King, 2020; Schubert et al., 2021; Szekeres & King, 2006; Wilk & Arrigo, 2020).…”
Section: Case Reportmentioning
confidence: 99%